MANFAAT SENAM VITALISASI OTAK TERHADAP FUNGSI KOGNITIF DAN GANGGUAN TIDUR PADA LANSIA - Widyastuti, K.; Karang, A.A.A.S.I.; Laksmidewi, A.A.A.P.; Adnyana, I.M.O.; Utami, D.K.I.; Witari, N.P.; Widyadharma, I.P.E. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i03.p07, 2023)
The increase in life expectancy influence the increment in the number of elderly and all challenges related to the aging process. Dementia as a neurodegenerative disease with symptoms of cognitive and behavioral disorders that affect the ability of the elderly to carry out social and work activities. Another problem seen in the elderly population is sleep disorder. The problem is memory and sleep disorders are often not considered as something that must be handled specifically and are often ignored even though these complaints greatly affect the quality of life of the elderly. This community service activity was directed to support efforts to improve elderly health services at Puskesmas, especially Puskesmas II West Denpasar. Activities carried out included brain vitalization exercise, examination of cognitive function and sleep disorders in the elderly, and providing counseling materials on dementia and insomnia in the elderly. The activity involved 18 elderly with an average age of 66.6±7.4 years. Sleep disorders screening examination with the Pittsburgh Sleep Quality Index found 16.7% elderly experienced sleep disorders, although sleep quality was still good in all elderly people. Cognitive function screening with the Indonesian version of the Montreal Cognitive Assessment examination found that 55.6% elderly had impaired cognitive function. This activity introduces the risk of impaired cognitive function and sleep disorders in the elderly, so that the elderly and their families can start activities and maintain health to prevent dementia and sleep disorders in the elderly. Keywords: elderly, cognitive, dementia, sleep disorder.